Manajemen Dana Pensiun Syariah - Efrita Norman; Enah Pahlawati (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
Pension Fund is a legal entity that is independent and separate from the employer, whose function is to manage and run a pension program in accordance with applicable regulations. In this regard, Pension Funds require a separate reporting system from the employer which aims to provide information about Pension Fund finances. The purpose of this research is to find out what are the differences between conventional pension funds and syari'ah pension funds and how to manage pension funds according to syari'ah. The analytical method used by the author is to use a qualitative approach, methodological qualitative research is an approach using deductive thinking in which a series of variables and research results are evidenced by cause and effect thinking, the type of research is literature study where the author in this study collects data with reading journals and books so that you will get accurate data and do in-depth analysis to find and get in-depth information about how to manage pension funds based on the principles of sharia which we now know as Sharia pension funds, the results are the basis of differentiation in pension funds conventional syari'ah is that shari'ah pension funds have several advantages including: having a contract in each transaction, having a shari'ah supervisory board and also when participants are late paying pension contributions they will be subject to permanent penalties. i the proceeds from the punishment funds will be allocated for social activities, so that there is an element of helping (atta'aun) fellow human beings.